Las interpretaciones de La casa de Bernarda Alba en los teatros húngaros en el siglo XXI - Katona, Eszter (Acta Hispanica, 2013)
Federico García Lorca’s last play, The House of Bernarda Alba was in fact his first drama that was presented to the Hungarian audience in the 1950s. Nearly sixty years have passed since then, and numerous Hungarian theaters have included this play in their repertoire. I managed to trace 19 premiers from the period of 1955-2000 and 25 since the turn of the century. However, behind these high numbers we do not always find traditional theatrical presentations working with Lorca’s text. Other adaptations, like dance or musical plays, were also inspired by Lorca’s drama, but with their different forms of expression they distinguished themselves from the traditional prose theater. Nevertheless, the presentation of these performances is important as well, as they contribute to the formation of Lorca’s image in the Hungarian audience. From these performances this study examines some of those from the first decade of the 21st century that, in some way, were significant, memorable or outstanding stagings.